TINJAUAN TERHADAP EKSISTENSI HAK ULAYAT DI MINANGKABAU (STUDI KASUS DI KENAGARIAN SUNGAI ANTUAN KECAMATAN MUNGKA, KABUPATEN LIMA PULUH KOTA, SUMATERA BARAT) - Devi Wulan Tari; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Communal land ownership is an important part of customary rights and is a very important factor in the life of Indonesian society, as well as indigenous people in West Sumatra that most of the population lives and livelihoods depend on the land. Article 3 of Law No. 5 of 1960 on Basic Regulation of Agrarian, containing a statement of recognition of the existence of customary rights of indigenous communities along by the fact still exist, meaning when in reality does not exist, then the customary rights that will not be turned on again, and will not be created new customary rights. According to the Customary Law Minangkabau communal land should not be traded, according to the slogan that live in Minangkabau society. But in reality there is still a violation of the rules of the customs. the purpose of the research is to know how the existence of customary rights in Kenagarian Antuan River, District Mungka, District Fifty City, West Sumatra, and how the role of the prince and Ninik Mamak and density Adat (KAN) customary rights in dispute resolution in Minangkabau. This research was conducted by using a sociological approach to research that want to see the correlation between law and society, with the specification in the form of descriptive research through library research. Based on this research, the existence of customary rights in Kenagarian Antuan River, District Mungka, District Fifty City, West Sumatra, began to weaken and occur several cases of customary rights, the role of Ninik Mamak, the prince is also not optimal because still there is a violation of their decision. Supposedly indigenous peoples and indigenous leaders to work together to protect customary rights, and people are given direction on customary rights and the role of traditional leaders should be optimized again.Keywords : Land Rights - Communal Land - Existence - Customary Law